2021
DOI: 10.24085/jsaa.v9i1.1431
|View full text |Cite
|
Sign up to set email alerts
|

Disguised Blessings amid Covid‑19: Opportunities and Challenges for South African University Students with Learning Disabilities

Abstract: The Covid‑19 pandemic has led to changes from traditional face-to-face teaching and learning to online systems. These changes have resulted in a concerted focus by local and international scholars on how some students are disadvantaged from accessing pedagogy due to a lack of resources and supportive living conditions that enable meaningful off‑campus learning. Simultaneously, disabilities in higher education is getting international attention, too, highlighting how students with disabilities are vulnerable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Elna's narrative resonates with some of the findings from Manase's (2021) recent study of fifteen students with various specific learning disabilities at one South African university. That study found that most participants reported experiencing better engagement with emergency remote online learning in a way that outweighed some notable challenges (Manase, 2021). ISSN 2523-1154…”
Section: C) Mode Of Teaching Preferencesmentioning
confidence: 58%
See 1 more Smart Citation
“…Elna's narrative resonates with some of the findings from Manase's (2021) recent study of fifteen students with various specific learning disabilities at one South African university. That study found that most participants reported experiencing better engagement with emergency remote online learning in a way that outweighed some notable challenges (Manase, 2021). ISSN 2523-1154…”
Section: C) Mode Of Teaching Preferencesmentioning
confidence: 58%
“…Against this background, some scholars have recently called for the need for South African HEIs not only to develop formal student mental health policies and strategies but also to ensure that these are constantly implemented, monitored, and evaluated if these institutions are to improve the learning outcomes of these students (Kaminer & Shabalala, 2019;Vergunst, 2017) Davids, 2020;Ned, McKinney, McKinney & Swartz, 2020). The available academic literature in refereed journals (Ndlovu, 2020;Ngubane-Mokiwa & Zongozz, 2021;Manase, 2021;Ntombela, 2022) has not specifically explored the experiences of students with mental health challenges.…”
Section: Context: Mental Health In Higher Educationmentioning
confidence: 99%
“…Students manifesting with some disability categories accessed learning in the same way as any other student without disabilities because of family support, unique exposure and associations with powerful identities that privileged them (Sherry 2009;Goodley 2013). An example relates to Manase (2021) who argued that students with learning disabilities interviewed in her study stated that they were comfortable with online platforms as they found them a less structured approach to learning, that afforded them engagement with their studies without distractions of big, overcrowded lecture-halls, that are intimidating and cause severe anxiety and panic attacks. Students with physical impairments were advantaged during the pandemic when they could access learning from home because they no longer had to manoeuvre the inaccessible built environment of the university (Ndlovu 2020).…”
Section: Intersectionality Consideration Of Difference Within Differencementioning
confidence: 99%
“…Intersectionality and context should not be overlooked where it concerns students with disabilities because they are not homogeneous (Goodley 2013). For example, on one hand, scholars such as Burgstahler (2015) have argued that students with learning disabilities have challenges with learning content because of their inability to independently process information as they lack skills and knowledge for time management (Manase 2021) while on the other, Crespo (2020) reported that some students with learning disabilities found online learning flexible and suitable for their learning needs. Such contradiction suggests that difference within differences needs to be considered when looking at pedagogy of students with disabilities largely and their epistemic access, in particular.…”
Section: Intersectionality Consideration Of Difference Within Differencementioning
confidence: 99%
See 1 more Smart Citation